2014
DOI: 10.1038/onc.2014.282
|View full text |Cite
|
Sign up to set email alerts
|

A combinatorial microRNA therapeutics approach to suppressing non-small cell lung cancer

Abstract: Targeted cancer therapies, while often effective, have limited utility due to preexisting primary or acquired secondary resistance. Consequently, agents are sometimes used in combination to simultaneously affect multiple targets. MicroRNA mimics are excellent therapeutic candidates because of their ability to repress multiple oncogenic pathways at once. Here we treated the aggressive Kras;p53 non-small cell lung cancer mouse model and demonstrated efficacy with a combination of two tumor-suppressive microRNAs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
182
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(185 citation statements)
references
References 34 publications
(45 reference statements)
3
182
0
Order By: Relevance
“…All these lines of evidence open up the possibility to target multiple players of the same pathway and give hope for combined therapeutic interventions. In line with this hypothesis, it has recently been shown that the simultaneous systemic delivery of two small non-coding RNAs acting as tumor suppressors, miR-34 and let-7, leads to reduced non-small lung cancer growth (33).…”
Section: Discussionmentioning
confidence: 83%
“…All these lines of evidence open up the possibility to target multiple players of the same pathway and give hope for combined therapeutic interventions. In line with this hypothesis, it has recently been shown that the simultaneous systemic delivery of two small non-coding RNAs acting as tumor suppressors, miR-34 and let-7, leads to reduced non-small lung cancer growth (33).…”
Section: Discussionmentioning
confidence: 83%
“…10,11 LncRNA-MALAT-1 was up-regulated during the tumourigenesis of lung cancer and demonstrated to be associated with metastasis in NSCLC patients. 12 Fas apoptotic inhibitory molecule 2 (FAIM2) could inhibit Fas-mediated cell death and was found to be overexpressed in SCLC cell lines.…”
mentioning
confidence: 99%
“…Two miRNA mimics (miR-34 and let-7) targeting oncogenes implicated in the development of solid tumors are presently in preclinical development [195]. miRNA antagonists are also of interest, with candidates under development: three miRNAs (miR-195 et miR-208/499) in preclinical targeting CVD and one miRNA (miR-122) in phase II clinical trial targeting hepatitis C viral infection [196,197].…”
Section: Therapymentioning
confidence: 99%